(untitled) (Journal of Enam Medical College, 2024)
Creutzfeldt-Jakob disease (CJD) is an extremely lethal and rapidly progressive spongiform encephalopathy caused by abnormal form of prion protein. It occurs worldwide with an estimated annual incidence about 1−2 cases per million populations. Several forms of the disease have been described−the most common is the sporadic type. Clinical features include briskly progressive dementia, myoclonus, visual or cerebellar signs, and pyramidal/extra-pyramidal signs. Diagnosis of CJD is usually challenging. Combining clinical features with laboratory parameters, electroencephalogram (EEG), and magnetic resonance imaging (MRI) of the brain expedites the diagnosis. It has no definitive treatment; only symptomatic and supportive managements are provided to the patients. Affected patients generally die within 1 year of the onset of illness. We report a 40-year-old lady who presented with 2 months’ history of rapidly progressive cognitive decline, vertigo and blurring of vision. Her diagnosis was made by classic findings on EEG, MRI of the brain along with clinical features and laboratory parameters. In spite of continuous supportive treatment, she died after 3 months from the onset of her illness. Early diagnosis, extensive research activities regarding prevention and treatment, raising social awareness and educating health care professionals about the disease might improve the current unsatisfying scenario of CJD. J Enam Med Col 2022; 12(1): 54−58